The Interaction of Student’s Creativity Thinking Skills Through Project Based Learning and Learning Cycle 7E in Parabolic Motion on the Second Grade Students of Senior High School - Dian Nafiah; Widha Sunarno; Suharno Suharno (Postgraduate, University of Mataram, 2023)
Creativity thinking skills is one of the competencies that must be possessed in the 21st century. Teachers must provide facilities for students to develop creative thinking skills through the selection of appropriate learning methods. This study aims to find out the interaction between student’s creativity thinking skills, Project Based Learning, and Learning Cycle 7E methods in Physics lesson chapter parabolic motion on XI grade students. The methods of this study are quasi experiment with two ways ANAVA design. This research was conducted at Al Islam 1 Senior High School Surakarta est Java Indonesia in August 2022. Sample of this study selected using the cluster random sampling technique. The research used was class XI 1 as Group 1 with Project Based Learning methods and XI 2 as Group 2 with Learning Cycle 7E methods. Based on the analysis data by using SPSS program at the significant level of 5% it can be concluded that there is interaction between student’s creativity thinking skills, Project Based Learning, and Learning Cycle 7E methods in Physics lesson chapter parabolic motion on XI grade students. It is also concluded that Project Based Learning give better impact to enhance student’s creativity thinking skills